The Alphabet of Galactolipids in Arabidopsis thaliana - Ibrahim, Amina; Schütz, Anna-Lena; Galano, Jean-Marie; Herrfurth, Cornelia; Feussner, Kirstin; Durand, Thierry; Brodhun, Florian; Feussner, Ivo (Frontiers in Plant Science, 2011)
Galactolipids constitute the major lipid class in plants. In recent years oxygenated derivatives of galactolipids have been detected. They are discussed as signal molecules during leaf damage, since they accumulate in wounded leaves in high levels. Using different analytical methods such as nuclear magnetic resonance, infra-red spectroscopy and high performance liquid chromatography/mass spectrometry (HPLC/MS) earlier reports focused on the analysis of either oxidized or non-oxidized species and needed high levels of analytes. Here, we report on the analysis of the galactolipid subfraction of the Arabidopsis leaf lipidome by an improved HPLC/MS2-based method that is fast, robust and comparatively simple in its performance. Due to a combination of phase partitioning, solid phase fractionation, liquid chromatography and MS2 experiments this method has high detection sensitivity and requires only low amounts of plant material. With this method 167 galactolipid species were detected in leaves of A. thaliana. Out of these 79 being newly described species. From all species the head group and acyl side chains were identified via MS2 experiments. Moreover, the structural identification was supported by HPLC/time-of-flight (TOF)-MS and gas chromatography (GC)/MS analysis. The quantification of different galactolipid species that accumulated 30 min after a mechanical wounding in A. thaliana leaves showed that the oxidized acyl side chains in galactolipids are divided into 65 % cyclopentenones, 27 % methyl-branched ketols, 3.8 % hydroperoxides/straight-chain ketols, 2.0 % hydroxides and 2.6 % phytoprostanes. In comparison to the free cyclopentenon derivatives, the esterifed forms occur in a 149-fold excess supporting the hypothesis that galactolipids might function as storage compounds for cyclopentenones. Additional analysis of the ratio of non-oxidized to oxidized galactolipid species in leaves of wounded plants was performed resulting in a ratio of 2.0 in case of monogalact